(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This study moved on to the phenomenon of the location of the study regarding the existence of some of the community users of health services in the Tahuna Barat Puskesmas about the inadequate quality of health services provided by puskesmas officers. Thus, this study aims to determine the extent of the influence of the work environment on service quality in the Tahuna Barat District Health Center, Sangihe Islands District. Using descriptive methods and quantitative approaches, the data collected through the distribution of Research Questionnaires (questionnaires) was analyzed using Frequency Table analysis techniques, while testing research hypotheses used statistical inferencing techniques, such as product moment correlation analysis techniques and simple linear regression.The results of data analysis show that (1) both the working environment (X) and the health service quality variable in the Tahuna Barat Puskesma are in the moderate to high category. (2) The results of correlation analysis and simple linear regression show that the work environment has a positive and significant effect on the quality of health services with a degree of determination of 38.9%. Thus, the results of this study empirically justify the underlying theories so that the hypothesis The work environment has a significant influence on the quality of services in the Tahuna Barat District Health Center, Sangihe Islands District, it can be accepted empirically very convincingly.Referring to the results of this study, it can be suggested: To improve the quality of service even higher, the management of the Tahuna Barat District Health Center, especially the local government of Sangihe Islands District, needs to conduct technical training for Puskesmas staff and nurses to improve their performance in providing health services people in need Keyword work : Enviroment, Service Quality, Health Center